Extracorporeal Membrane Oxygenation in Pregnancy: An Analysis of the Extracorporeal Life Support Organization Registry. Issue 5 (May 2020) - Ramanathan, Kollengode; Tan, Chuen Seng; Rycus, Peter; Anders, Marc; Lorusso, Roberto; Zhang, John J. Y.; MacLaren, Graeme
Abstract : Objectives: We examined data from the International Registry of the Extracorporeal Life Support Organization to identify risk factors for mortality in pregnant and peripartum patients receiving extracorporeal membrane oxygenation. Design: Retrospective analysis. Setting: International Registry of Extracorporeal Life Support Organization. Patients: We collected de-identified data on all peripartum patients who needed extracorporeal membrane oxygenation between 1997 and 2017 using International Classification of Diseases, 9th and 10th Edition criteria. Interventions: Our primary outcome measure was in-hospital mortality. We also collected data on demographics, preextracorporeal membrane oxygenation ventilator, hemodynamic and biochemical parameters, extracorporeal membrane oxygenation mode, duration, and complications. Initial bivariate analysis assessed potential associations between survival and various preextracorporeal membrane oxygenation as well as extracorporeal membrane oxygenation-related factors. Variables with p values of less than 0.1 were considered for logistic regression analysis which identified predictors of mortality. Measurements and Main Results: There were 280 peripartum patients who received extracorporeal membrane oxygenation. Overall maternal survival was 70%, with observed mortality for these patients decreasing over the 21-year time period. Multivariate regression identified extracorporeal cardiopulmonary resuscitation (odds ratio, 3.674; 95% CI, 1.425–9.473; overall p = 0.025), duration of extracorporeal membrane oxygenation (< 66 hr: odds ratio, 1; 66–128 hr: odds ratio, 0.281; 95% CI, 0.101–0.777; p = 0.014; 128–232 hr: odds ratio, 0.474; 95% CI, 0.191–1.174; p = 0.107; and > 232 hr: odds ratio, 1.084; 95% CI, 0.429–2.737; p = 0.864; overall p = 0.017), and renal complications on extracorporeal membrane oxygenation (odds ratio, 2.346; 95% CI, 1.203–4.572; p = 0.012) as significant risk factors for mortality. There was no statistically significant difference in mortality between venovenous versus venoarterial versus mixed group extracorporeal membrane oxygenation (23.9 vs 34.4 vs 29.4%; p = 0.2) or between pulmonary versus cardiac indications (1.634; 95% CI, 0.797–3.352; p = 0.18) for extracorporeal membrane oxygenation. Conclusions: On analysis of this multicenter database, pregnant and peripartum patients with refractory cardiac or respiratory failure supported on extracorporeal membrane oxygenation had survival rates of 70%. We identified preextracorporeal membrane oxygenation as well as extracorporeal membrane oxygenation-related factors that are associated with mortality. Abstract : Supplemental Digital Content is available in the text.